Prevalence and risk factors for postnatal mental health problems in mothers of infants admitted to neonatal care: analysis of two population-based surveys in England - Jenny Gong; Gracia Fellmeth; Maria A. Quigley; Chris Gale; Alan Stein; Fiona Alderdice; Siân Harrison (My University, 2023)
Background Previous research suggests that mothers whose infants are admitted to neonatal units (NNU) experience higher rates of mental health problems compared to the general perinatal population. This study examined the prevalence and factors associated with postnatal depression, anxiety, post-traumatic stress (PTS), and comorbidity of these mental health problems for mothers of infants admitted to NNU, six months after childbirth. Methods This was a secondary analysis of two cross-sectional, population-based National Maternity Surveys in England in 2018 and 2020. Postnatal depression, anxiety, and PTS were assessed using standardised measures. Associations between sociodemographic, pregnancy- and birth-related factors and postnatal depression, anxiety, PTS, and comorbidity of these mental health problems were explored using modifed Poisson regression and multinomial logistic regression. Results Eight thousand fve hundred thirty-nine women were included in the analysis, of whom 935 were mothers of infants admitted to NNU. Prevalence of postnatal mental health problems among mothers of infants admitted to NNU was 23.7% (95%CI: 20.6–27.2) for depression, 16.0% (95%CI: 13.4–19.0) for anxiety, 14.6% (95%CI: 12.2–17.5) for PTS, 8.2% (95%CI: 6.5–10.3) for two comorbid mental health problems, and 7.5% (95%CI: 5.7–10.0) for three comorbid mental health problems six months after giving birth. These rates were consistently higher compared to mothers whose infants were not admitted to NNU (19.3% (95%CI: 18.3–20.4) for depression, 14.0% (95%CI: 13.1–15.0) for anxiety, 10.3% (95%CI: 9.5–11.1) for PTS, 8.5% (95%CI: 7.8–9.3) for two comorbid mental health problems, and 4.2% (95%CI: 3.6–4.8) for three comorbid mental health problems six months after giving birth. Among mothers of infants admitted to NNU (N=935), the strongest risk factors for mental health problems were having a long-term mental health problem and antenatal anxiety, while social support and satisfaction with birth were protective. Conclusions Prevalence of postnatal mental health problems was higher in mothers of infants admitted to NNU, compared to mothers of infants not admitted to NNU six months after giving birth. Experiencing previous mental health problems increased the risk of postnatal depression, anxiety, and PTS whereas social support and satisfaction with birth were protective. The fndings highlight the importance of routine and repeated mental health assessments and ongoing support for mothers of infants admitted to NNU.
Keywords: Neonatal unit, Perinatal, Depression, Anxiety, Posttraumatic stress, Maternity survey, Mental health